Crystalline Ultrastructures, Inflammatory Elements, and Neoangiogenesis Are Present in Inconspicuous Aortic Valve Tissue. (28th December 2010) - Dorfmüller, P.; Bazin, D.; Aubert, S.; Weil, R.; Brisset, F.; Daudon, M.; Capron, F.; Brochériou, I.
Abstract : Morbidity from calcific aortic valve disease (CAVD) is increasing. Recent studies suggest early reversible changes involving inflammation and neoangiogenesis. We hypothesized that microcalcifications, chemokines, and growth factors are present in unaffected regions of calcific aortic valves. We studied aortic valves from 4 patients with CAVD and from 1 control, using immunohistochemistry, scanning electron microscopy, and infrared spectrography. We revealed clusters of capillary neovessels in calcified (ECC), to a lesser extent in noncalcified (ECN) areas. Endothelial cells proved constant expression of SDF-1 in ECC, ECN, and endothelial cells from valvular surface (ECS). Its receptor CXCR4 was expressed in ECC. IL-6 expression correlated with CXCR4 staining and presence of lymphocytes. VEGF was expressed by ECS, its receptor by ECC and ECN. Crystalline ultrastructures were found on the surface of histologically noncalcified areas (HNCAs), spectrography revealed calcium hydroxylapatite. Our results demonstrate that crystalline ultrastructures are present in HNCAs, undergoing neoangiogenesis in an inflammatory context. These alterations could be an early witness of disease and an opening to therapy.